COMMUNITY KNOWLEDGE AS A DRIVER OF PARTICIPATION IN MANGROVE ECOSYSTEM MANAGEMENT: A CASE STUDY FROM SEBESI ISLAND, INDONESIA - Erina Hartati; Adelia Desya Putri; Mingga Ayu Saputri; Putri Sania; Syariah Nursyina Arrum; Wulan Dwi Ganarsih; Wanda Julia; Bunga Erya Padela; David Julian; Muhammad Reza (Jurusan Perikanan dan Kelautan, 2026)
Coastal areas play an important role in supporting the economic, social, and environmental aspects of communities, one of which is through the presence of mangrove ecosystems. Mangroves have vital ecological and economic functions, such as protecting shorelines from abrasion, providing habitats for marine organisms, and serving as a source of livelihood for coastal communities. Sebesi Island in Lampung is one of the regions with a fairly extensive mangrove ecosystem; however, its management has not yet fully involved the local community. This study aims to determine the relationship between community knowledge and participation in the management of the mangrove ecosystem on Sebesi Island. Data were collected through questionnaires, interviews, and field observations. The analysis results show a positive and significant relationship between the level of knowledge and community participation, with a Pearson correlation coefficient of 0.551 and a significance level of 0.002. These findings indicate that increasing community understanding can encourage greater involvement in sustainable mangrove management.